DEVELOPMENT OF ANDROID-BASED LEARNING MEDIA WITH STEM PROJECTS FOR JUNIOR HIGH SCHOOL IN SCIENCE LEARNING - Ilham, M.Rifki; Oktavia, Rani (Department of Science Education, 2024)
The application of Information and Communication Technology (ICT) in the field of education includes the use of multimedia facilities and internet media in the learning process. This is line with the demands of the 21st century, namely the need for human resources with 4C skills. Therefore, in the field of education must use a curriculum that supports this. The Merdeka Curriculum is a curriculum that encourages 4C skills in education. In the field of 21st century education it is closely related to the STEM approach which is a discipline in the world of education. Learning with the STEM approach is learning that combines four disciplines, namely Science, Technology, Engineering and Mathematics by focusing on two or more fields in the learning process so that students are active in solving problems in the real world. One way to integrate STEM into learning is through learning media. The type of this research is Research and Development (R&D). The development model used is the ADDIE model which consists of the stages of analysis, design, development, implementation and evaluation. This research was only conducted up to the development stage. The instruments used in this study were teacher and student interview sheets, validity test questionnaires and practical test questionnaires. The research data is calculated using the Moment Kappa (k) formula to analyze the results of the validity and practicality test of android-based learning media. The results of the validity test obtained an average kappa moment (k) value of 0.86 with a very high validity category. The results of the practice test on teachers obtained an average kappa (k) moment value of 0.96 with a very high practicality category and the results of the practical test on students obtained an average kappa (k) moment value of 0.84 with a very high practicality category . Based on these results, it means that Android-based learning media is integrated with STEM projects on substance material and its changes are valid and practical.